A case series of sarcomatoid transitional cell carcinoma of renal pelvis and collecting duct carcinoma of kidney (Indian Journal of Case Reports, 2018)
Sarcomatoid transitional cell carcinoma (TCC) of the renal pelvis and collecting duct carcinoma (CDC) of the kidney are rare types of malignant renal tumors with aggressive behavior. Here, we report a case series of these tumors, in males of age 65 years and 72 years, respectively. In both the cases, the left kidney was affected and they underwent the left-sided radical nephroureterectomy. Histologically, sarcomatoid TCC showed two components with invasive TCC and areas with spindle cells and osteoclastic type of giant cells. The immunohistochemistry showed diffuse positivity for CK7 and negativity for CK20 and p63 in both the components. CDC showed tubule-papillary patterns with marked desmoplasia. The patients were disease free after a follow-up of 12 months and 2½ years, respectively, without any adjuvant therapy.